Effect of sealing strategy on the temperature distribution and smoke spread behavior in inclined mine roadway: A numerical study - Ruizhi Guo; Li Ma; Jing Fan; Pengyu Zhang; Wenbo Gao; Yuheng Jiang (Case Studies in Thermal Engineering)
Sealing strategy is widely employed in coal mine fire extinguishing. To investigate the effects of sealing strategy on the temperature distribution, smoke back-layering length (SB-LL), and self-extinction time, the Fire Dynamics Simulator (FDS) is used to simulate the inclined roadway fires with the heat release rate (HRR) of 4 MW, roadway slopes (0°, 5°, 10°, and 20°) and sealing ratios (0 %–100 %). The relationship between the maximum temperature beneath the ceiling (TC) and sealing ratio (θ) and roadway slope (α) is analyzed by the dimensionless method. The results show that as the roadway slope increases, the maximum TC of the roadway fire decreases and its position continues to shift downstream, and the SB-LL becomes shorter. For small roadway slope, the weak stack effect is insufficient to stop smoke backflow. As the sealing ratio increases, the SB-LL and the maximum TC rise significantly, and the position continues to move to the fire source. For inclined roadway fires, the fire self-extinguishing requires a 100 % sealing ratio, and the self-extinction time decreases with the increase of the roadway slope. This research has important theoretical and practical significance for the control of mine roadway fires.